Using GA Approach to Solve a Deteriorating Inventory Model in a normal Marketing Channel - Jonas C.P. Yu (International Journal of Supply Chain Management, 2017)
This study discusses how to use integrated marketing channel in order to reach the marketplace with lower cost or more profit, and how a framework for analysis can improve the channel decision made by an executive acting as a channel manager or designer. This paper also proposes a manufacturer-distributor-retailer deteriorating inventory system that contains three levels of normal marketing channel. In order to achieve long-term benefits and global optimum of the system, the different facilities should develop their partnership through information sharing or stratgic alliances. The mathematical model describes how the integrated approach to decision making can achieve global optimum by Genetic Algorithm(GA) method.